Where they lie : a novel - Coughlan, Claire (New York : Harper Perennial, 2024)
In 1968 Dublin, Nicoletta Sarto, an ambitious junior reporter for the Irish Sentinel, investigates the 25-year-old mystery of actress Julia Bridge's disappearance and her link to a woman who facilitated abortions, and becomes immersed in the illegal abortion industry, stirring up long-buried secrets from her own past.
Keywords: Women journalists -- Fiction; Motion picture actors and actresses -- Fiction; Murder -- Fiction; Abortion -- Fiction; Secrecy -- Fiction; Dublin (Ireland) -- Fiction; Thrillers (Fiction); Historical fiction; Novels